1959
DOI: 10.1113/jphysiol.1959.sp006274
|View full text |Cite
|
Sign up to set email alerts
|

The site of action of phlorrhizin in inhibiting intestinal absorption of glucose

Abstract: The effect of phlorrhizin in inhibiting glucose absorption from the intestine both in vivo and in vitro is well established, but the mode of action is still un-known. The present work was undertaken in an attempt to locate the site of action of phlorrhizin in the intestine. It was done concurrently with the experiments using a different technique recently reported by Parsons, Smyth & Taylor (1958) and supports theif conclusion that one action of phlorrhizin is to prevent the entry of glucose into the epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

1961
1961
1979
1979

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 11 publications
7
28
0
Order By: Relevance
“…If the potential in our experiments is due to sodium, a more rapid transfer of cations from the lumen is suggested. Newey, Parsons & Smyth (1959) have shown that the entry of glucose into the mucosal cells is prevented by phlorrhizin, and the present findings would suggest that phlorrhizin affects sodium entry, not necessarily directly, but possibly by preventing glucose entry. This is of interest in relation to the suggestion of Crane, Miller & Bihler (1961) that there is a direct relationship between sodium transfer and glucose transfer by the intestine.…”
Section: Proceedings Of the Physiologicalsupporting
confidence: 64%
“…If the potential in our experiments is due to sodium, a more rapid transfer of cations from the lumen is suggested. Newey, Parsons & Smyth (1959) have shown that the entry of glucose into the mucosal cells is prevented by phlorrhizin, and the present findings would suggest that phlorrhizin affects sodium entry, not necessarily directly, but possibly by preventing glucose entry. This is of interest in relation to the suggestion of Crane, Miller & Bihler (1961) that there is a direct relationship between sodium transfer and glucose transfer by the intestine.…”
Section: Proceedings Of the Physiologicalsupporting
confidence: 64%
“…Parsons et al (1958) found that phlorrhizin in concentrations of less than 5 x 10-4 M had little effect on oxygen consumption of the intestine, and Newey, Parsons & Smyth (1959) showed that at these concentrations phlorrhizin inhibited the entry of glucose into the cell from the luminal side, with only a small effect on metabolism. These findings showed that phlorrhizin had effects on cellular processes involved in glucose transfer, quite apart from its effect on glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Ponz (1952) suggested that uranyl ions function as nonpenetrating inhibitors of glucose absorption in the rat intestine and Ponz & Lluch (1958), using an in vivo technique, observed that the intestinal transfer of glucose and galactose was diminished in the presence of uranyl ions while transfer of fructose and arabinose was unaffected. Since at least part of the hexose transfer mechanism is close to the luminal border of the cell (Newey, Parsons & Smyth, 1959) it was of interest to investigate the effect of uranyl ions on hexose transfer by an in vitro technique.…”
Section: Introductionmentioning
confidence: 99%